Database-driven Spatial Data Auditing using QGIS against LDAP Authentication and Authorization - Gaikwad, Santosh; Bhagat, Maulik; Odedra, Arjan; Rahul Kanani; Saraswat, Aditya (International Journal of Computer Sciences and Engineering, 2022)
Efficient spatial database management system is now considered to be a primary component of any GIS architecture or Spatial Data Infrastructure (SDI) which acts as a central repository that disseminates data across web and desktop clients. In such scenarios, a common requirement for production databases is the ability to track history and authenticity of the data generated. Using the database and the trigger system as regular practice, it’s possible to add history tracking, however, there exists a challenge of using desktop GIS tools for editing and validation of the normalized data residing in spatial databases, intacting data integrity with privileged and authenticated users. Considering the facts and importance of auditing, jurisdiction based user access management and limitation of editing spatial data in a web browser, the present study is an attempt to develop an Open Source solution based on authorization and authentication against LDAP, QGIS, PostgreSQL/PostGIS, and Multicorn FDW software.